Perbedaan Konsumsi Hedonis pada Mahasiswa Universitas Syiah Kuala Ditinjau dari Jenis Kelamin dan Asal Fakultas - Cut Aya Riadhah; Risana Rachmatan (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
This research aims to study the difference of hedonic consumption among syiah kuala university students in term of gender and faculties. The technique sampling used were purposive and quota sampling with 360 students consisted of 180 male and 180 female from 12 faculties. The data were collected using hedonic consumption scale constructed by researcher based on Hirschman and Holbrook theory (1982). Coefisien reliability of this research was (α)= 0,873. Hypothesis was tested by using Independent Sample T-Test which showed significance value 0,000 (p<0,05) and One Way Anova which showed significance value 0,000 (p<0,05). Result shows that there was different hedonic consumption between male and female students of Unsyiah in which female indicated higher hedonic consumption than male student. Besides, students of dentistry faculty indicated higher hedonic consumption than the other faculties.